2017
DOI: 10.1038/srep41102
|View full text |Cite
|
Sign up to set email alerts
|

Excessive activation of ionotropic glutamate receptors induces apoptotic hair-cell death independent of afferent and efferent innervation

Abstract: Accumulation of excess glutamate plays a central role in eliciting the pathological events that follow intensely loud noise exposures and ischemia-reperfusion injury. Glutamate excitotoxicity has been characterized in cochlear nerve terminals, but much less is known about whether excess glutamate signaling also contributes to pathological changes in sensory hair cells. I therefore examined whether glutamate excitotoxicity damages hair cells in zebrafish larvae exposed to drugs that mimic excitotoxic trauma. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 71 publications
(87 reference statements)
0
50
0
1
Order By: Relevance
“…While it has been unclear whether hair cell death is due to a direct effect on hair cells or due to an indirect effect via receptors present on the afferent fibers innervating the hair cells (44), a recent study in zebrafish has shown that excess glutamate signaling through ionotropic glutamate receptors induces hair cell death irrespective of the presence or absence of nerve fibers (45). Compounds 13142 and 13222 may therefore prevent aminoglycoside-induced hair cell death by blocking Ca 2+ entry into hair cells via NMDA receptors (41,42,46).…”
Section: Discussionmentioning
confidence: 99%
“…While it has been unclear whether hair cell death is due to a direct effect on hair cells or due to an indirect effect via receptors present on the afferent fibers innervating the hair cells (44), a recent study in zebrafish has shown that excess glutamate signaling through ionotropic glutamate receptors induces hair cell death irrespective of the presence or absence of nerve fibers (45). Compounds 13142 and 13222 may therefore prevent aminoglycoside-induced hair cell death by blocking Ca 2+ entry into hair cells via NMDA receptors (41,42,46).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies of the mammalian cochlea have recently revealed that even a single incidence of noise overexposure can produce cochlear synaptopathy and neurodegeneration, exacerbating age-related hearing loss (Kujawa and Liberman, 2009;Lin et al, 2011). A major advance toward understanding this synaptopathy is to determine the cause of the initial excitotoxic insult.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation as to why we are observing adverse 547 effects in wildtype fish upon incubation with (±)-Bay K 8644 in not only the acoustic startle but 548 also in the distribution of CTBP2 puncta and the absolute smooth orientation is that excessive 549 cytosolic calcium (altering calcium homeostasis) in the hair cell can be detrimental (Esterberg et 550 al., 2013). Another explanation could be that the elevated cytosolic calcium in the wildtype hair 551 cells due to (±)-Bay K 8644 could be causing excessive activation of the glutamate receptors 552 that has been linked to apoptotic hair-cell death (Sheets, 2017). We may be observing this 553 affect across various assessments with only (±)-Bay K 8644, in the wildtype animals because it 554 is the more potent drug.…”
Section: Discussion 293mentioning
confidence: 99%